Agensi dan Kewarganegaraan Inklusif bagi Perempuan Penyandang Disabilitas: Studi Kasus Peran HWDI dalam Penanganan Covid-19 di Jakarta - Salsabila Widyadhari; Sri Lestari Wahyuningroem (Jurnal Perempuan, 2023)
Persons with disabilities experience vulnerability in fulfilling their right to protection in a pandemic situation This study aims to examine the participation process of groups of persons with disabilities, namely the Indonesian Association of Women with Disabilities (Himpunan Wanita Disabilitas Indonesia – HWDI) through the struggle for disability protection during the Covid-19 period in DKI Jakarta. This study uses the perspective of inclusive citizenship to see efforts to involve active participation of citizens in encouraging the fulfillment of rights by the government. This study uses a descriptive qualitative method with narrative analysis techniques. The results of the study show that although HWDI has been able to influence the DKI Jakarta provincial government in several policies, there are rights that still need to be fulfilled in the dimension of inclusive citizenship. These rights include social, civil, and political rights which have not been fulfilled by the government, which has implications for persons with disabilities not being further involved in handling the Covid-19 pandemic.